The Study of Thermodynamics of Thermoplastic Explosive at 71°C. (October 2019) - Gao, Zan; Jin, Penggang; Ren, Songtao; Yang, Jian
Abstract: A testing system was established to measure at 71°C the expansion pressure of a thermoplastic explosive with different charge quantities and of thermoplastic explosives with the same charge quantity but different formulations. It is indicated that the growth of expansion pressure of the thermoplastic explosive is non-linear with the increase rate of the charge quantity. And the expansion pressure has the possibility of decreasing when the charge quantity reaches a certain value. The expansion pressure will vary remarkably with the selection of polymer materials with differed dynamic mechanical properties as additives.